2017
DOI: 10.1159/000485536
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Induces Autophagic Cell Death and Inhibits Invasion and Metastasis of Human Osteosarcoma Cells in An Autophagy-Dependent Manner

Abstract: Background/Aims: Osteosarcoma (OS) is the most common primary malignant tumor of bone tissue. Although treatment effectiveness has improved, the OS survival rate has fluctuated in recent years. Andrographolide (AG) has been reported to have antitumor activity against a variety of tumors. Our aim was to investigate the effects and potential mechanisms of AG in human osteosarcoma. Methods: Cell viability and morphological changes were assessed by MTT and live/dead assays. Apoptosis was detected using Annexin V-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…A study has shown halofuginone‐induced autophagy suppresses breast cancer cell migration and invasion . Meanwhile, in osteosarcoma cells, the activation of autophagy is associated with the suppression of EMT . In the study, we used 3‐MA to inhibit autophagy and observed the effects of TQ on migration, invasion and EMT in RCC cell lines 786‐O and ACHN.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown halofuginone‐induced autophagy suppresses breast cancer cell migration and invasion . Meanwhile, in osteosarcoma cells, the activation of autophagy is associated with the suppression of EMT . In the study, we used 3‐MA to inhibit autophagy and observed the effects of TQ on migration, invasion and EMT in RCC cell lines 786‐O and ACHN.…”
Section: Discussionmentioning
confidence: 99%
“…Several therapy, such as osteroprotegerin, RANK-Fc, PTHrp antibodies, and Vitamin-D analogues, are under phase I to III studies. Other target therapy, such as anti-MMP-9,anti-IGF-1R, Quercetin, Osthole and activating aromatic hydrocarbon receptor, were reported in rescent [120, 122-126]. Current treatments mainly target the RANK-RANKL pathway and PTHrP signaling.…”
Section: Therapeutic and Molecular Interventionsmentioning
confidence: 99%
“…18,19 Therefore, we also examined the effect of XAG on autophagy and its relation to metastasis inhibition. 18,19 Therefore, we also examined the effect of XAG on autophagy and its relation to metastasis inhibition.…”
Section: Xag Induces Autophagy In Hcc Cellsmentioning
confidence: 99%
“…Numerous studies have shown a crucial role of autophagy in tumor metastasis, several natural compounds exhibit anti-metastatic activity through induction or inhibition of autophagy. 18,19 Therefore, we also examined the effect of XAG on autophagy and its relation to metastasis inhibition. Following a 24-hour XAG treatment, the formation of AVO was detected by acridine orange staining as an indicator of autophagy.…”
Section: Xag Induces Autophagy In Hcc Cellsmentioning
confidence: 99%
See 1 more Smart Citation